(untitled) (Orfeu, 2021)
This article presents a brief examination of the creative processes and practices in music observed during the period of empirical research corresponding to the work done during a master’s degree. The work aimed at understanding the network of meanings and musical values that guide educational practices at Casa Pequeno Davi and its relations in the construction of an environment favorable to creative musical expression. The qualitative research carried out an ethnographic case study in the aforementioned local field, comprising three musical courses / workshops given by the music teachers of the NGO, named, P1, P2 and P3. The epistemological bases that supported the analysis of the data collected in the field worked on the conjugation between the habitus (of the musician, institutional) and the social representations (of music), in a constant dialogue that are established within themes related to music education, creativity, and social vulnerability.